2019
DOI: 10.1177/0300985819861721
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Extracellular Traps, Cell-Free DNA, and Immunothrombosis in Companion Animals: A Review

Abstract: Immunothrombosis is a potentially beneficial physiological process that aids innate immunity and host defense against pathogen invasion. However, this process can also be damaging when it occurs to excess or in critical blood vessels. Formation of extracellular traps by leukocytes, particularly neutrophils, is central to our understanding of immunothrombosis. In addition to degranulation and phagocytosis, extracellular traps are the third mechanism by which neutrophils combat potential pathogens. These traps c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 235 publications
1
56
0
2
Order By: Relevance
“…Calprotectin contributes to the antimicrobial activity of NETs by binding of zinc and manganese, but that property can also be responsible for cell and tissue damage . Methods for NET assays in body fluids have included quantitation of cell‐free DNA and neutrophil elastase, and there are ELISA methods for quantification of MPO‐DNA complexes, so‐called NET remnants . However, detection of calprotectin in complexes with a major DNA component by an immunoassay would give improved specificity and also allow rapid testing of large number of samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calprotectin contributes to the antimicrobial activity of NETs by binding of zinc and manganese, but that property can also be responsible for cell and tissue damage . Methods for NET assays in body fluids have included quantitation of cell‐free DNA and neutrophil elastase, and there are ELISA methods for quantification of MPO‐DNA complexes, so‐called NET remnants . However, detection of calprotectin in complexes with a major DNA component by an immunoassay would give improved specificity and also allow rapid testing of large number of samples.…”
Section: Introductionmentioning
confidence: 99%
“…NETs contribute to the production of autoantibodies against citrullinated proteins in RA . NET release from neutrophils is emerging as an important factor in thrombogenesis, so‐called immunothrombosis, which takes place in sepsis (ie disseminated intravascular coagulation) and malignancy . Multiple myeloma is a typical example of a serious disease with immune imbalance and increased levels of proinflammatory cytokines such as IL‐6 and IL‐1 .…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled activation of these factors leads to immune induced disease pathogenesis through excessive inflammation. In humans and other mammals, neutrophil activation directly contributes to tissue damage through the release of neutrophil extracellular traps (NETs) 38,39 . Functional studies to compare cytokine secretion and NET release in response to infectious agents could confirm that genetic differences in innate immunity contribute to differences in disease susceptibility and outcomes between Asian and African elephants.…”
Section: Discussionmentioning
confidence: 99%
“…Though there exists a lack of consensus on the origins of circulating cell-free DNA, it is believed that circulating levels are related cellular breakdown and active DNA-release mechanisms in host cells [31]. The concept of neutrophil extracellular traps, or NETs, involves the release of web-like scaffolds of cell-free DNA composed of extracellular chromatin which can enhance antimicrobial activity in the face of an infectious stimulus [32]. A model utilizing canine neutrophils has revealed that high-dose lipopolysaccharide stimulates the cells to undergo the production of NETs in vitro [33].…”
Section: Discussionmentioning
confidence: 99%